Is the protein folding an aim-oriented process? Human haemoglobin as example. (10th May 2007) - Brylinski, Michal; Konieczny, Leszek; Roterman, Irena
The model for protein folding (in silico) simulation is presented. Three steps have been implemented: early stage folding based on the backbone conformation; hydrophobic collapse based on the fuzzy-oil-drop model; aim-oriented structure modification by the function-related ligand. The model has been verified taking α and β haemoglobin chains as examples to fold them in two different conditions: with and without haem being present in the folding environment. The presence of haem and its participation in the folding simulation led to the structure more similar to the crystal one. It suggests that the haem presence directs the folding process towards the function-related structure.